Cyber conflict or democracy "hacked"? How cyber operations enhance information warfare. Issue 1 (14th September 2020) - Whyte, Christopher
Abstract: Are cyber-enabled information warfare (IW) campaigns uniquely threatening when compared with traditional influence operations undertaken by state actors? Or is the recent "hacking" of Western democracies simply old wine in new—but fundamentally similar—bottles? This article draws on classical theories of democratic functionality from the political science and communications studies fields to deconstruct the aims and effects of cyber-enabled IW. I describe democracies as information systems wherein the moderating functions of democratic discourse and policy deliberation rely on robust mechanisms for asserting the credibility, origination, and quality of information. Whereas the institutions of democracy are often compromised in ways that force failures of the system's moderating dynamics, influence operations in the digital age act to subvert the traditional mechanisms of democratic functionality in new ways. Sophisticated digital age information operations create a multifaceted attribution challenge to the target state that amounts to unprecedented uncertainty about the nature and scope of the threat. However, the promise of cyber-enabled IW capabilities emerges more from the rewiring of modern democratic information environments around new media platforms than it does from the cyber conflict faculties of state actors. Rather, cyber operations act as an adjunct modifier of IW abilities that allow belligerent governments to secure new sources of private information, to divert attention from other pillars of IW campaigns, to compromise the capabilities of domestic counterintelligence assets and to tacitly coerce important members of society.